2020
DOI: 10.1002/ejhf.2032
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound imaging of congestion in heart failure: examinations beyond the heart

Abstract: Congestion, related to pressure and/or fluid overload, plays a central role in the pathophysiology, presentation and prognosis of heart failure and is an important therapeutic target. While symptoms and physical signs of fluid overload are required to make a clinical diagnosis of heart failure, they lack both sensitivity and specificity, which might lead to diagnostic delay and uncertainty. Over the last decades, new ultrasound methods for the detection of elevated intracardiac pressures and/or fluid overload … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
107
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 91 publications
(208 reference statements)
1
107
0
6
Order By: Relevance
“…Perhaps non‐cardiologists have admitted the value of ultrasound more than cardiologists despite the background we have as cardiologists and despite the tricky haemodynamic situation we are frequently facing 14–16 . In the present issue of the Journal, Pellicori et al 17 . provide a highly comprehensive use of echocardiography for guiding the treatment of our heart failure patients.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…Perhaps non‐cardiologists have admitted the value of ultrasound more than cardiologists despite the background we have as cardiologists and despite the tricky haemodynamic situation we are frequently facing 14–16 . In the present issue of the Journal, Pellicori et al 17 . provide a highly comprehensive use of echocardiography for guiding the treatment of our heart failure patients.…”
Section: Figurementioning
confidence: 95%
“…Another question that comes out of the reading of Pellicori et al . manuscript 17 is the following: should we teach also general practitioners and nurse practitioners? They could up‐titrate the medical treatments after hospitalization to prevent recurrent decompensations potentially better if they could get this non‐invasive assessment of the haemodynamic condition of each patient.…”
Section: Figurementioning
confidence: 99%
“…It can be detected by biomarkers and imaging tools for the diagnosis, prognostic evaluation and, possibly, to guide treatment, in patients with acute HF 3–7 . Pellicori et al 8 . reviewed ultrasound methods for the detection and quantification of congestion, including imaging of the heart, lungs (B‐lines), kidneys (intrarenal venous flow) and venous system (inferior vena cava and internal jugular vein diameter).…”
Section: Acute Heart Failurementioning
confidence: 99%
“…1 Sodium and water retention affects a variety of organs, including the heart itself, the lungs, and the kidneys. 2 Loop diuretics have been the cornerstone of congestion management in HF for more than 50 years. 3 Although they have never been shown to decrease mortality in randomized trials, decades of routine clinical use has shown that intravenous administration of loop diuretics results in rapid diuresis and decongestion in the majority of patients admitted for worsening HF.…”
mentioning
confidence: 99%
“…Patients without clinical signs of congestion may have biological or echocardiographic signs of congestion, and those signs are associated with HF hospitalizations. 1,2 Before withholding loop diuretics, verifying that patients do not have pulmonary congestion evidenced by lung ultrasound or a dilated inferior vena cava suggesting raised systemic venous pressure could provide additional assurance of clinical stability.…”
mentioning
confidence: 99%